2022
DOI: 10.21834/ebpj.v7i19.3240
|View full text |Cite
|
Sign up to set email alerts
|

Youth and their Knowledge on the Sustainable Development Goals (SDGs)

Abstract: The Sustainable Development Goals (SDGs) under the United Nations (UN) have highlighted the youth as the stakeholders. Their knowledge of the triple bottom line of sustainability (economic, social, and environmental) is a prerequisite for SDG accomplishment. This paper investigates the level of SDGs knowledge among university youth. It was discovered that youth at the Universiti Teknologi MARA (UiTM), Malaysia have a moderate understanding of SDGs and need to be attentive to environment-related SDGs. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…On the other hand, the main source of information about SDGs was formal education for respondents from Croatia. This finding is in accordance with previous studies, where formal education and lessons were the primary sources of information on SD (Yuan et al 2021;Ismail et al 2022;Leiva-Brondo et al 2022).…”
Section: Results and Disccusionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, the main source of information about SDGs was formal education for respondents from Croatia. This finding is in accordance with previous studies, where formal education and lessons were the primary sources of information on SD (Yuan et al 2021;Ismail et al 2022;Leiva-Brondo et al 2022).…”
Section: Results and Disccusionsupporting
confidence: 93%
“…Respondents were more familiar with the definition, aspects and dimensions of SD where the answer accuracy was greater than 90%. These findings were similar to those of Ismail et al (2022), who stated that students possess certain knowledge about SDGs. Respondents were less familiar with technical aspects of SDGs such as timelines, national governance systems and MDGs, but they were most familiar with inclusivity aspects of SDGs (Ismail et al 2022).…”
Section: Table 2: Source Of Informationsupporting
confidence: 90%
See 2 more Smart Citations
“…In Malaysia as a whole, the study of sustainability awareness in general among university students has been conducted recently by many researchers [28,[31][32][33][34][35][36][37], supporting the importance of this study. A study on youth studying in public and private educational institutions in Penang found that they have a high level of awareness of the concept of sustainable development issues and are willing to practice a more sustainable lifestyle [32,34].…”
Section: Introductionmentioning
confidence: 69%